2023
DOI: 10.7554/elife.83685
|View full text |Cite
|
Sign up to set email alerts
|

Zooanthroponotic transmission of SARS-CoV-2 and host-specific viral mutations revealed by genome-wide phylogenetic analysis

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a generalist virus, infecting and evolving in numerous mammals, including captive and companion animals, free-ranging wildlife, and humans. Transmission among non-human species poses a risk for the establishment of SARS-CoV-2 reservoirs, makes eradication difficult, and provides the virus with opportunities for new evolutionary trajectories, including the selection of adaptive mutations and the emergence of new variant lineages. Here, we use publi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Knowing when and where a zoonotic outbreak is likely to occur, namely when a virus whose normal host is an animal species gains the ability to cross the species barrier and causes infection in humans, remains an enormous challenge (Hernandez-Castro et al, 2022). Notably, evolutionary tools have enabled analyses of the transmission of SARS-CoV-2 between human and non-human species and to identify mutations associated with each species (Naderi et al, 2023), where for instance animal-to-human transmission from minks was detected to be higher compared with lower transmission from other species (cats, dogs, and deer). Hence, continuous molecular surveillance of SARS-CoV-2 from animals is paramount to reveal new insights into SARS-CoV-2 host range and adaptation, contributing to our understanding of the risk of reinfection from animal reservoirs back into humans (Naderi et al, 2023).…”
Section: Tracking the Origins And Evolution Of Sars-cov-2 In Real Timementioning
confidence: 99%
See 1 more Smart Citation
“…Knowing when and where a zoonotic outbreak is likely to occur, namely when a virus whose normal host is an animal species gains the ability to cross the species barrier and causes infection in humans, remains an enormous challenge (Hernandez-Castro et al, 2022). Notably, evolutionary tools have enabled analyses of the transmission of SARS-CoV-2 between human and non-human species and to identify mutations associated with each species (Naderi et al, 2023), where for instance animal-to-human transmission from minks was detected to be higher compared with lower transmission from other species (cats, dogs, and deer). Hence, continuous molecular surveillance of SARS-CoV-2 from animals is paramount to reveal new insights into SARS-CoV-2 host range and adaptation, contributing to our understanding of the risk of reinfection from animal reservoirs back into humans (Naderi et al, 2023).…”
Section: Tracking the Origins And Evolution Of Sars-cov-2 In Real Timementioning
confidence: 99%
“…replicate) in a human cell and transmit from person-to-person (Randolph & Rogers, 2010). Multiple genetic changes are often required, though we do not typically know a priori how many or which specific environmental conditions promote their evolution (Naderi et al, 2023;Visher et al, 2021). The principles governing the evolution of novelty suggest that any factor which increase the likelihood of a rare mutation contributing to a novel trait, either through genetic mechanisms like gene amplification or ecological ones like increased population size, can enhance the chance that novelty will evolve (Kassen, 2019).…”
Section: Zoonotic Outbreaks and Vector Dispersalmentioning
confidence: 99%
“…Instead, species-specific selective pressures on Spike might explain the differences in pN/pS. Through genome-wide association studies (GWAS), we previously identified three significantly mink-associated and 26 deer-associated SNVs (Naderi et al, 2023). These SNVs are putative species-specific adaptations that should therefore be under species-specific positive selection.…”
Section: Tests For Selection On Within-host Diversitymentioning
confidence: 99%
“…Since the beginning of the ongoing COVID-19 pandemic, SARS-CoV-2 has been transmitted from humans to many different animal species, and viral variants of concern could potentially evolve in a non-human animal. Previously, using available whole genome consensus sequences of SARS-CoV-2 from four commonly sampled animals (mink, deer, cat, and dog) we inferred similar numbers of transmission events from humans to each animal species but a relatively high number of transmission events from mink back to humans (Naderi et al, 2023). Using a genome-wide association study (GWAS), we identified 26 single nucleotide variants (SNVs) that tend to occur in deer – more than any other animal – suggesting a high rate of viral adaptation to deer.…”
mentioning
confidence: 96%
“…Mutations in Nsp13 are associated with species-specific and geographical adaptation of SARS-CoV-2, and targeting Nsp13 is known to impair SARS-CoV-2 replication (56)(57)(58)(59). Also, substitutions in Nsp13 of CoVs severely affect replication and viral propagation (58)(59)(60)(61)(62).…”
Section: Nsp13 Promotes Cell Death In Sars-cov-2 Infected Cells and I...mentioning
confidence: 99%